Write All These Down: Essays on Music - Kerman, Joseph (Berkeley, CA University of California Press, 1994)
Eminent, wide-ranging, and wonderfully readable, Kerman's writing on musicology, opera, Beethoven, and Elizabethan music has informed and inspired an extensive audience both in America and abroad. There is much to interest both the general reader and the musicologist in this collection of twenty essays. Included are several notable pleas addressed by Kerman to his professional colleagues in an effort to get them to adopt a more critical orientation for their work. Other essays range from a moving account of William Byrd as a spokesman for the beleaguered Elizabethan Catholic minority to a discerning analysis of Beethoven's well-known obsession with the key of C minor. The controversial tenets of Kerman's classic 'Opera as Drama' (1956) are reaffirmed in essays on Don Giovanni, The Magic Flute, Tristan und Isolde, Ernani and I Lombardi. He offers challenging models for a humane and historically informed music criticism. An added gem is the Preface, which provides an intellectual and anecdotal road map of the place of the essays in Kerman's academic and public expeditions.
Keywords: 20th Century (1901-2000); Music history; Musical analysis; USA